Engineering cytokines for cancer immunotherapy: a systematic review - Fu, Yong; Tang, Renhong; Zhao, Xiaofeng (Frontiers in Immunology, 2023)
Cytokines are pivotal mediators of cell communication in the tumour microenvironment. Multiple cytokines are involved in the host antitumour response, but the production and function of these cytokines are usually dysregulated during malignant tumour progression. Considering their clinical potential and the early successful use of cytokines in cancer immunotherapy, such as interferon alpha-2b (IFNα-2b; IntronA®) and IL-2 (Proleukin®), cytokine-based therapeutics have been extensively evaluated in many follow-up clinical trials. Following these initial breakthroughs, however, clinical translation of these natural messenger molecules has been greatly limited owing to their high-degree pleiotropic features and complex biological properties in many cell types. These characteristics, coupled with poor pharmacokinetics (a short half-life), have hampered the delivery of cytokines via systemic administration, particularly because of severe dose-limiting toxicities. New engineering approaches have been developed to widen the therapeutic window, prolong pharmacokinetic effects, enhance tumour targeting and reduce adverse effects, thereby improving therapeutic efficacy. In this review, we focus on the recent progress and competitive landscape in cytokine engineering strategies and preclinical/clinical therapeutics for cancer. In addition, aiming to promote engineered cytokine-based cancer immunotherapy, we present a profound discussion about the feasibility of recently developed methods in clinical medicine translation.